Training and Organizational Support as Predictors of Instructor Performance with Job Satisfaction as an Intervening Variable - Jazus Sudirman; Suhana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of training and organizational support on the performance of instructors at the Vocational Training Center (BLK) of the Ministry of Manpower in Semarang, with job satisfaction as a mediating variable. The research employed a quantitative approach by distributing questionnaires to 130 active instructors. Data analysis was conducted through validity and reliability testing, as well as regression analysis using SPSS software. The results indicate that training has a positive effect on both job satisfaction and instructor performance. Organizational support also significantly influences job satisfaction, although its direct effect on performance is relatively moderate. Job satisfaction was found to mediate the relationship between training and organizational support on instructor performance. These findings highlight the importance of relevant training design and consistent organizational support to enhance instructor performance in the context of online learning. The current research has theoretical and practical implications.